Field testing of a spectrum-splitting transmissive concentrator photovoltaic module. (August 2019) - Robertson, John; Riggs, Brian; Islam, Kazi; Ji, Yaping Vera; Spitler, Christopher M.; Gupta, Naman; Krut, Dimitri; Ermer, Jim; Miller, Fletcher; Codd, Daniel; Escarra, Matthew
Abstract: Hybrid photovoltaic-thermal systems can decouple IR light from visible light, allowing it to be collected separately by spectrum-optimized mechanisms for increased total efficiency. To demonstrate this, we have designed and prototyped a transmissive spectrum-splitting concentrator photovoltaic module that maximizes solar energy conversion by utilizing the entire solar spectrum. The system first collects visible light using IR-transmissive triple-junction photovoltaic cells to achieve an in-band module efficiency of η m I B = 34.7% for light of wavelengths λ < 870 nm. Simultaneously, 58.8% of light with λ > 870 nm is transmitted through the cells for collection by a thermal receiver. By combining electrical and thermal power collection, 75% of incident solar power is collected, far surpassing the collection capability of only photovoltaics. The module was tested on a dual-axis tracked parabolic concentrator dish at up to 160 suns for 60 cumulative on-sun hours while maintaining photovoltaic cell temperatures at an average of 50 °C via active cooling. The system performed as expected based on modeled values, and represents a cost-effective path forward for dual-generation of electricity and high-temperature heat with increased total efficiency. The capability is valuable in a wide range of commercial and industrial cogeneration applications. Graphical abstract: Image 108644 Highlights: A spectrum-splitting photovoltaic module is prototyped for use in solar cogeneration. Module photovoltaic regions show 34.7% in-band electrical conversion efficiency. Module photovoltaic regions transmit 58.8% of infrared light to a thermal receiver. Module is field tested at 160 suns, showing 75% of incident solar power is collected. Design enables low temperature PV operation with high temperature process heat capture.